2017
DOI: 10.1007/s40262-017-0509-5
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetic Model and Pharmacokinetic Target Attainment of Micafungin in Intensive Care Unit Patients

Abstract: ObjectiveTo study the pharmacokinetics of micafungin in intensive care patients and assess pharmacokinetic (PK) target attainment for various dosing strategies.MethodsMicafungin PK data from 20 intensive care unit patients were available. A population-PK model was developed. Various dosing regimens were simulated: licensed regimens (I) 100 mg daily; (II) 100 mg daily with 200 mg from day 5; and adapted regimens 200 mg on day 1 followed by (III) 100 mg daily; (IV) 150 mg daily; and (V) 200 mg daily. Target atta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 33 publications
7
22
1
Order By: Relevance
“…A two-compartment model with first order elimination best described the micafungin plasma concentrations, which is in line with previous reports. 5,12,[18][19][20] In our study, body weight was the size descriptor best explaining the inter-individual variability in clearance, where individual clearance (in L/h) is predicted using the power function 0.69 * (weight / 70) 0.74 . This relation is supported by previously reported clearances in normal-weight healthy subjects.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…A two-compartment model with first order elimination best described the micafungin plasma concentrations, which is in line with previous reports. 5,12,[18][19][20] In our study, body weight was the size descriptor best explaining the inter-individual variability in clearance, where individual clearance (in L/h) is predicted using the power function 0.69 * (weight / 70) 0.74 . This relation is supported by previously reported clearances in normal-weight healthy subjects.…”
Section: Discussionmentioning
confidence: 65%
“…These patients show an increased micafungin clearance and an augmented dose of 200 mg has been proposed previously. 12,20 In obese critically ill patients, a significant lower probability of target attainment was reported compared to normal-weight critically ill patients. 19 Although a 300 mg dose was not investigated in this study, this should be considered in critically ill obese patients, if possible under the guidance of therapeutic drug monitoring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Are sensitive to azoles, therapy with an echinocandin is recommended as it was shown to be superior in a septic ICU population with invasive candidiasis and candidaemia [53,54]. Several population pharmacokinetic studies in a general ICU population suggested that echinocandins are probably underdosed and no dose reduction is required for patients on CRRT [55,56].…”
Section: De-escalationmentioning
confidence: 99%
“…Simulations show that only 62% of patients reach the MIC/AUC target for non- C. parapsilosis spp. ; therefore, these patients could benefit from a dose escalation to micafungin 200 mg, as indicated in the manufacturer’s label information [ 62 ].…”
Section: Special Populationsmentioning
confidence: 99%